Analisis Trend Efisiensi dan Efektifitas Pendapatan Asli Daerah di Kabupaten Kepulauan Siau Tagulandang Biaro - Alfrets Ronald Takarendehang; Daisy S. M Engka; Mauna Th.B. Maramis (Riviera Publishing, 2025)
The purpose of this study is to analyze the efficiency and effectiveness of regional financial management on the economic development of the Sitaro Islands Regency in 2018-2024 and its development during 2025-2031. The data analysis method used in this study is a qualitative research method with a case study approach. The results of the study indicate that financial management efficiency for the 2018-2025 period falls within the inefficient criteria. Restaurant Tax and Street Lighting Tax contribute more than other types of regional taxes. The development of financial management efficiency for the 2025-2031 period, based on data analysis from 2018-2024, has decreased, while the effectiveness of regional original revenue realization in 2018-2024 fluctuated from fairly effective, effective, and very effective, with developments declining although still within the effective criteria.